Common breast feeding problems in mothers in early postnatal period - R., Yogendra Prasad; P., Chandrakala; G., Manasa (International Journal of Contemporary Pediatrics, 2017)
Background: Breast feeding is the optimal method of feeding in infants and provides improved short and long term health outcomes. The objective of this study was to identify common breast feeding problems in mothers in early postnatal period. Methods: Four hundred and ninety-four mothers in early postnatal period admitted in Kempegowda Institute of Medical Sciences and Research Centre were enrolled in this study during the period from March 2016 to June 20016.All the mothers were questioned regarding about their knowledge of breast feeding, health education received during Antenatal visits, the problems during breast feeding and were also observed for any mistakes of mothers during breast feeding. Results: In this study, the age of the mothers was in the range between 18-38 years. Out of them most were house wives (87.5%) and from urban area (78.4%). This study showed lacking antenatal education of mothers about breast feeding. Among the study group only about 13% had the knowledge about breast feeding, which reflects real breast feeding problems especially in the postnatal period which is critical period in starting and continuation of breast feeding. Among the problems encountered, majority of the mothers had no experience how to hold the baby in right position for breast feeding (16.5%), mothers believed that milk was not sufficient (13%) and the refusal of the baby to suckle (8.7%). Conclusions: This study clearly shows that there is lack of knowledge regarding importance of breast feeding and its benefits to the baby by mothers, during antenatal visits which leads to all problems during breast feeding and hence has to be tackled earlier during pregnancy by educating them about breast feeding.